Reduced human platelet uptake by pig livers deficient in the asialoglycoprotein receptor 1 protein. (27th February 2015) - Paris, Leela L.; Estrada, Jose L.; Li, Ping; Blankenship, Ross L.; Sidner, Richard A.; Reyes, Luz M.; Montgomery, Jessica B.; Burlak, Christopher; Butler, James R.; Downey, Susan M.; Wang, Zheng‐Yu; Tector, Matthew; et al.
Abstract Background The lethal thrombocytopenia that accompanies liver xenotransplantation is a barrier to clinical application. Human platelets are bound by the asialoglycoprotein receptor (ASGR) on pig sinusoidal endothelial cells and phagocytosed. Inactivation of the ASGR1 gene in donor pigs may prevent xenotransplantation‐induced thrombocytopenia. Methods Transcription activator‐like effector nucleases (TALENs) were targeted to the ASGR1 gene in pig liver‐derived cells. ASGR1 deficient pig cells were used for somatic cell nuclear transfer (SCNT). ASGR1 knock out (ASGR1−/−) fetal fibroblasts were used to produce healthy ASGR1 knock out piglets. Human platelet uptake was measured in ASGR1+/+ and ASGR1−/− livers. Results Targeted disruption of the ASGR1 gene with TALENs eliminated expression of the receptor. ASGR1‐/‐ livers phagocytosed fewer human platelets than domestic porcine livers during perfusion. Conclusions The use of TALENs in liver‐derived cells followed by SCNT enabled the production of healthy homozygous ASGR1 knock out pigs. Livers from ASGR1‐/‐ pigs exhibit decreased human platelet uptake. Deletion of the ASGR1 gene is a viable strategy to diminish platelet destruction in pig‐to‐human xenotransplantation.